Eco-friendly production of biosurfactant by Mucor circinelloides UCP 0018 using agro-industrial substrates (Research, Society and Development, 2022)
Green bioconversion of low-cost agro-industrial substrates into high-value-added products becomes a biotechnological strategy to enable the production on an industrial scale. In this context, two agro-industrial by-products were used in this study in order to formulate an economic and sustainable media for biosurfactant (BS) production by Mucor circinelloides UCP 0018. For this, a 22 full-factorial design was used to investigate the influence of concentrations of corn steep liquor (CSL) and crude glycerol (CG) on surface tension as response variable. The results showed the ability of this Mucoralean fungus to produce BS under all design conditions, highlighting condition 4 (9% of both substrates) due to the greater reduction in surface tension (from 72 to 29.7 mN/m). Statistical analysis confirmed significant influence of both by-products on surface tension. This BS exhibited excellent emulsifying properties (EI24 98.9%), as well as ODA of 28.26 cm², with burnt motor oil. Preliminary characterization showed the polymeric nature of the biomolecule, with a content of 55.7% of carbohydrates, 28.2% of lipids and 16.1% of proteins, as well as its anionic character and critical micellar dilution (CMD) at 50%. The stability in the range of pH 2-6, temperature 20-80°C and salinity 5-25% evidenced a stable BS, with promising potential of application in several industrial activities or environmental processes in adverse conditions.